Hybrid identities : theoretical and empirical examinations - Iyall Smith, Keri E., 1973-; Leavy, Patricia, 1975- (Studies in critical social sciences, 2008)
Hybrid identities continue to be predominant in minority or immigrant communities, but these are not the only sites of hybridity in the globalized world. Combining theoretical and empirical pieces, this book explores the theoretical work seeking to describe hybrid identities, and illustrates the application of these theories in empirical research.